Putting health equity at heart of universal coverage—the need for national programmes of action - Friedman, Eric A; Gostin, Lawrence O; Kavanagh, Matthew M; Periago, Mirta Roses; Marmot, Michael; Coates, Anna; Binagwaho, Agnes; Mukherjee, Joia; Chowdhury, Mushtaque; Robinson, Tracy; Veloso, Valdiléa G; Wang, Chenguang; et al. (BMJ, 2022)
This article was published in BMJ [Copyright © 2019, BMJ Publishing Group Ltd] and the definite version is available at: https://doi.org/10.1136/bmj.l5901. The Journal's website is at: https://www.bmj.com/content/367/bmj.l5901